If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 1) + -1 = 2 + -1(5 + 2x) Reorder the terms: 7(1 + x) + -1 = 2 + -1(5 + 2x) (1 * 7 + x * 7) + -1 = 2 + -1(5 + 2x) (7 + 7x) + -1 = 2 + -1(5 + 2x) Reorder the terms: 7 + -1 + 7x = 2 + -1(5 + 2x) Combine like terms: 7 + -1 = 6 6 + 7x = 2 + -1(5 + 2x) 6 + 7x = 2 + (5 * -1 + 2x * -1) 6 + 7x = 2 + (-5 + -2x) Combine like terms: 2 + -5 = -3 6 + 7x = -3 + -2x Solving 6 + 7x = -3 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 6 + 7x + 2x = -3 + -2x + 2x Combine like terms: 7x + 2x = 9x 6 + 9x = -3 + -2x + 2x Combine like terms: -2x + 2x = 0 6 + 9x = -3 + 0 6 + 9x = -3 Add '-6' to each side of the equation. 6 + -6 + 9x = -3 + -6 Combine like terms: 6 + -6 = 0 0 + 9x = -3 + -6 9x = -3 + -6 Combine like terms: -3 + -6 = -9 9x = -9 Divide each side by '9'. x = -1 Simplifying x = -1
| -7(x+10)-x-2=-8(x+7)-16 | | F+25=31.25 | | (3b-3)(4b+5)= | | 1.2y=1.44 | | -6(-4z+6z^2)+3(4z-4z^2)= | | 25y+30y^2+12y-18y^2= | | m+9=-23 | | m+9=23 | | .5x+6-2x+.5=7.2 | | -5(-5y-6y^2)-6(-2y+3y^2)= | | 14w=-70 | | 2a+4=2a+10 | | 2a+4=-2a+10 | | 2a+4=-2a-10 | | 4(2e+3e^2)+6(-3e-4e^2)= | | Y^2+19y+78=0 | | 5x+1=-4x-17 | | 4x-22x+10=0 | | 5x+1=4x+17 | | 12mn^2+6mn= | | y^2-9=-49 | | -.10(87)+.65x=.05(x-6) | | -10+7(x-2)=10(2x-5) | | -4x+8=2(-2x+4) | | 4y+24=-28 | | 4y+24=28 | | 8.41=0.058*x | | X^2-2X-1000=0 | | 4x-19+2x-5=180 | | 1.2*x=54 | | X+9.15=17 | | 2x+13=75 |